2022
DOI: 10.1161/jaha.121.023806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cardiac Arrest Centers on the Survival of Patients With Nontraumatic Out‐of‐Hospital Cardiac Arrest: A Systematic Review and Meta‐Analysis

Abstract: Background The role of cardiac arrest centers (CACs) in out‐of‐hospital cardiac arrest care systems is continuously evolving. Interpretation of existing literature is limited by heterogeneity in CAC characteristics and types of patients transported to CACs. This study assesses the impact of CACs on survival in out‐of‐hospital cardiac arrest according to varying definitions of CAC and prespecified subgroups. Methods and Results Electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 76 publications
2
19
1
Order By: Relevance
“… 7 Although the definition of CACs varies widely, it is often understood as having high annual OHCA volume and the capability to deliver a bundle of interventions. 8 Our finding of improved survival in high-volume centers supports this recommendation. However, closer inspection of the studies that reported aORs revealed that PCI, extracorporeal membrane oxygenation, and TTM capabilities were not adjusted for by most studies.…”
Section: Discussionsupporting
confidence: 68%
“… 7 Although the definition of CACs varies widely, it is often understood as having high annual OHCA volume and the capability to deliver a bundle of interventions. 8 Our finding of improved survival in high-volume centers supports this recommendation. However, closer inspection of the studies that reported aORs revealed that PCI, extracorporeal membrane oxygenation, and TTM capabilities were not adjusted for by most studies.…”
Section: Discussionsupporting
confidence: 68%
“…This was corroborated by the 2021 European Resuscitation Council guidelines [9,44 ▪ ]. Since the release of these guidelines, an updated meta-analysis in 2021 based on 36 studies found significant improvement in survival with favourable neurological outcome (adjusted odds ratio [aOR] 1.85, 95% confidence interval [CI] 1.52–2.26) and survival (aOR 1.92, 95% CI 1.59–2.32) among patients treated at CACs [45 ▪ ]. CACs were self-declared by study authors and capable of relevant interventions.…”
Section: What Are Cardiac Arrest Centres?mentioning
confidence: 81%
“…However, it remains unclear which patient subgroups would benefit most from treatment at a CAC. The aforementioned meta-analysis performed a subgroup analysis and found that the treatment effect of CACs was more pronounced among patients with shockable rhythm and without prehospital ROSC [45 ▪ ]. This analysis, however, should be interpreted carefully in light of smaller sample sizes and known selection bias by EMS.…”
Section: Who When and Where To Transport?mentioning
confidence: 99%
“…For a long time, previous studies examining institutional volume and patient prognosis have failed to show consensus on various aspects of this association [ 10 18 ]. A recently published systematic review has shown that cardiac arrest centers may improve the prognosis of OHCA patients [ 18 , 26 ], but it is inconclusive as to whether OHCA patients should be transported directly to a cardiac arrest center [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous analysis suggested that the treatment effect of cardiac arrest centers may be significantly better for patients with shockable rhythm and without prehospital ROSC [ 26 ]. The results of this study indicate that patients with prehospital ROSC are more likely to benefit from high-volume hospitals, although there was no significant difference between institutional volume and patient outcomes in patients without prehospital ROSC.…”
Section: Discussionmentioning
confidence: 99%